2018
DOI: 10.1182/bloodadvances.2018021162
|View full text |Cite
|
Sign up to set email alerts
|

Severe aplastic anemia: allogeneic bone marrow transplantation as first-line treatment

Abstract: Treatment of severe aplastic anemia has improved significantly over the past 4 decades. This review will summarize the key areas of progress in the use of allogeneic hematopoietic cell transplantation and nontransplant immunosuppressive therapy (IST) for the treatment of aplastic anemia and then summarize the recommendations for first-line treatment. Based on recent data, we argue that guidelines for the initial treatment of patients with newly diagnosed severe aplastic anemia require revision. At the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 83 publications
2
86
0
1
Order By: Relevance
“…This risk also seemed to increase with aging . So hematologists tended to pursue a better FFS, and it was recommended that HSCT was preferable to IST no matter the donor was HLA‐matched or haploidentical . Our previous study also showed a trend of higher FFS in patients older than 40 years of age in 8th year after HID‐HSCT compared with those only received IST .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This risk also seemed to increase with aging . So hematologists tended to pursue a better FFS, and it was recommended that HSCT was preferable to IST no matter the donor was HLA‐matched or haploidentical . Our previous study also showed a trend of higher FFS in patients older than 40 years of age in 8th year after HID‐HSCT compared with those only received IST .…”
Section: Discussionmentioning
confidence: 80%
“…Hematopoietic stem cell transplantation (HSCT) has been generally accepted as the only method able to cure severe aplastic anemia (SAA). According to the current algorithm, HSCT was recommended as upfront therapy for young patients with a matched donor . Considering the high transplantation‐related mortality (TRM) rate, priority was given to immune suppression treatment (IST) in patients older than 40 years.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Other authors have reported equivalent OS between MRD and URD transplants in this patient population . While the 4‐year OS of 69% for our URD BMT patients is closer to that reported in other international studies, the 4‐year OS of 81% for the MRD BMT cases is lower than the 90%‐100% range reported in others countries and by international registries …”
Section: Discussionmentioning
confidence: 99%